Spontaneous Ultraslow Na+ Fluctuations in the Neonatal Mouse Brain - Lisa Felix; Daniel Ziemens; Gerald Seifert; Christine R. Rose (Cells, 2019)
In the neonate forebrain, network formation is driven by the spontaneous synchronized activity of pyramidal cells and interneurons, consisting of bursts of electrical activity and intracellular Ca2+ oscillations. By employing ratiometric Na+ imaging in tissue slices obtained from animals at postnatal day 2−4 (P2−4), we found that 20% of pyramidal neurons and 44% of astrocytes in neonatal mouse hippocampus also exhibit transient fluctuations in intracellular Na+. These occurred at very low frequencies (~2/h), were exceptionally long (~8 min), and strongly declined after the first postnatal week. Similar Na+ fluctuations were also observed in the neonate neocortex. In the hippocampus, Na+ elevations in both cell types were diminished when blocking action potential generation with tetrodotoxin. Neuronal Na+ fluctuations were significantly reduced by bicuculline, suggesting the involvement of GABAA-receptors in their generation. Astrocytic signals, by contrast, were neither blocked by inhibition of receptors and/or transporters for different transmitters including GABA and glutamate, nor of various Na+-dependent transporters or Na+-permeable channels. In summary, our results demonstrate for the first time that neonatal astrocytes and neurons display spontaneous ultraslow Na+ fluctuations. While neuronal Na+ signals apparently largely rely on suprathreshold GABAergic excitation, astrocytic Na+ signals, albeit being dependent on neuronal action potentials, appear to have a separate trigger and mechanism, the source of which remains unclear at present.